2012
DOI: 10.1007/s13369-012-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Cement and Silica Fume Treated Columns to Improve Peat Ground

Abstract: Peat layers are weak; much weaker and more compressible than inorganic soils, and thus do not provide suitable support for most engineering structures. The usual methods have been either to remove peat and replace it with suitable soil or to pass piles through it to the stronger soil layers below. On the other hand, research has been carried out to discover ways to strengthen peat deposits by deep stabilization. Peat was reinforced with precast columns stabilized with cement and silica fume. Unconfined compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…In consideration of the swampy environment of peatland, hydraulic binders are suitable for consuming water during the hydration process, thus enhancing peat strength. Similar results have been reported in previous studies on peat stabilization using cement and silica [7,30,31].…”
Section: Standard Compactionsupporting
confidence: 92%
See 3 more Smart Citations
“…In consideration of the swampy environment of peatland, hydraulic binders are suitable for consuming water during the hydration process, thus enhancing peat strength. Similar results have been reported in previous studies on peat stabilization using cement and silica [7,30,31].…”
Section: Standard Compactionsupporting
confidence: 92%
“…Materials 2021, 14, x FOR PEER REVIEW 7 of 24 have been reported in previous studies on peat stabilization using cement and silica [7,30,31].…”
Section: Ucs Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Meng et al [19] studied influences of compound nano calcium carbonate on strength and microstructure of soil-cement in marine environment and indicated that marine environment had large influences on strength and durability of soilcement. Kalantari et al [20] indicated that silicon powder had improved the strength and bearing capacity of soilcement. Kolias et al [21] and Karpisz and Jaworski [22] studied the influences of fly ash on the strength and stability of soil-cement.…”
Section: Introductionmentioning
confidence: 99%